Adverse events during vitreoretinal surgery under adequacy of anesthesia guidance: risk factor analysis - Stasiowski, Michał Jan; Pluta, Aleksandra; Lyssek-Boroń, Anita; Król, Seweryn; Krawczyk, Lech; Niewiadomska, Ewa; Żak, Jakub; Kawka, Magdalena; Dobrowolski, Dariusz; Grabarek, Beniamin Oskar; Szumera, Izabela; Koss, Michael Janusz; et al. (Pharmaceuticals, 2022)
Vitreoretinal surgeries require the administration of general anesthesia (GA) in selected groups of patients. The administration of intraoperative rescue narcotic analgesia (IRNA) during GA poses the risk of postoperative nausea and vomiting (PONV). The surgical pleth index (SPI), a crucial component of the adequacy of anesthesia (AoA) guidance of GA, optimizes the intraoperative titration of IRNA. The current analysis evaluated the risk factors for the occurrence of PONV and the oculo-cardiac reflex (OCR) in patients undergoing pars plana vitrectomy (PPV) under AoA guidance. In total, 175 patients undergoing PPV were randomly allocated to receive either GA with SPI-guided IRNA administration using fentanyl alone or in addition to different preoperative analgesia techniques. Any incidence of PONV or OCR was recorded. Obesity, overweight, smoking status, motion sickness, postoperative intolerable pain perception, female gender, fluid challenge and arterial hypertension did not correlate with an increased incidence of PONV or OCR under AoA guidance. Diabetes mellitus, regardless of insulin dependence, was found to correlate with the increased incidence of PONV. The AoA regimen including SPI guidance of IRNA presumably created similar conditions for individual subjects, so no risk factors of the occurrence of PONV or OCR were found, except for diabetes mellitus. We recommend using AoA guidance for GA administration to reduce OCR and PONV rates.
Gesehen am 21.11.2022